2020
DOI: 10.14245/ns.2040228.114
|View full text |Cite
|
Sign up to set email alerts
|

The Biportal Endoscopic Posterior Cervical Inclinatory Foraminotomy for Cervical Radiculopathy: Technical Report and Preliminary Results

Abstract: The purpose of the current study was to introduce a surgical technique for posterior cervical inclinatory foraminotomy (PCIF) using a percutaneous biportal endoscopic (BE) approach. Consecutive 7 patients underwent BE-PCIF for their cervical radiculopathy. Postoperative radiologic images (x-rays, computed tomography [CT], and magnetic resonance imaging [MRI]) were evaluated postoperatively for optimal neural decompression status and stability. A visual analogue scale (VAS) for the arm pain and the Neck Disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…Zdeblick et al [ 17 ] reported that instability slightly increased with a facet resection rate of up to 50%, but markedly increased with a facet resection rate of 75%. Chang et al [ 18 ] and Song and Lee [ 12 ] reported that undercutting the facet joint via an inclinatory surgical route is essential in terms of preserving the facet joint and capsule [ 12 , 18 ], further reporting favorable clinical outcomes. The 2 endoscopy groups in this study utilized a higher inclination angle when undercutting the facet joint and subsequently preserved the facet joint better than the microscopy group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zdeblick et al [ 17 ] reported that instability slightly increased with a facet resection rate of up to 50%, but markedly increased with a facet resection rate of 75%. Chang et al [ 18 ] and Song and Lee [ 12 ] reported that undercutting the facet joint via an inclinatory surgical route is essential in terms of preserving the facet joint and capsule [ 12 , 18 ], further reporting favorable clinical outcomes. The 2 endoscopy groups in this study utilized a higher inclination angle when undercutting the facet joint and subsequently preserved the facet joint better than the microscopy group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, uniportal endoscopy with a 12° endoscopic view can reveal the deeper foraminal space even if the preserved facet joint interferes with the surgical viewing compared to biportal endoscopy with a zero-degree endoscopic view. Although biportal endoscopic and microscopic surgery can achieve cervical posterior inclinatory foraminotomy using the contralateral-sided endoscopic approach [ 12 ] and anterior cervical retractor system [ 18 ], respectively, ipsilateral-sided conventional surgeries might have less ability to make a higher inclinatory surgical route than uniportal endoscopic surgery. Making an inclinatory surgical route is challenging during microscopic PCF because the spinous process restricts the direction of resection, and almost all patients had a nearly vertical approach angle when using this technique (mean negative SFAA, -1.0°±1.7°).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Lately, due to advancements in endoscopic spine surgery, the unilateral biportal endoscopic (UBE) technique has been applied in the cervical, thoracic and lumbar spine. [12][13][14][15] For extraforaminal stenosis at L5-S1, the UBE technique, which can go further into the extraforaminal lesion less invasively, is becoming widespread and surpassing microscopic surgery in popularity. The purpose of this study is to present the UBE technique for complete decompression of extraforaminal stenosis at L5-S1 and evaluate 1-year clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%